EKSAMINASI PUTUSAN KPPU MENGENAI RAHASIA PERUSAHAAN YANG MENGAKIBATKAN PERSAINGAN USAHA TIDAK SEHAT: Examination Of KPPU Decisions Regarding Company Confidential That Might Lead To Unfair Business Practices - Mayva, Verandha; Anggraini, Anna Maria Tri (Faculty of Law, Universitas Trisakti, 2024)
The guideline for article 23 of Law Number 5 of 1999 not yet approved, making company secrets andcriteria for company secrets often equated with the meaning of Trade Secret as regulated in Law Number30 of 2000 concerning Trade Secrets. The main problem is whether the information in the contractagreement between the musician and the recording company and company data about DMO in thecontract for the procurement of goods and/or services are included in the criteria for company secretsaccording to the perspective of business competition law and whether the decision of the panel of judgesin decision number 19/KPPU-L/ 2007 and number 35/KPPU-I/2010 are correct. This research usingnormative legal research by secondary and primary data. This research is descriptive and conclusionswith deductive reasoning. The results are, the essence the two decisions both discuss company secretswhich must keep the secret because it has economic value and if it open to the public will bring losses tothe company whose secrets are leaked so that both of them are included in the criteria of companysecrets in the perspective of business competition law. The decisions must contains more sanction onpenal law.